A numerical method for solving continuous population models for single and interacting species - Elçin Gökmen; Elçin Çelik (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In thisstudy, a numerical approach is presented to obtain the approximate solutions ofcontinuous population models for single and interacting species. This method isessentially based on the truncated Taylor series and its matrix representationswith collocation points. By using Taylor polynomials and collocation points,this method transforms population models into a matrix equation. The matrixequation corresponds to a system of nonlinear equations with the unknown Taylorcoefficients. To illustrate reliability and efficiency of the method, numericalexamples are presented and results are compared with the other numericalmethods. Additionally, residual correction procedure is applied to estimate theabsolute errors. All numerical computations have been performed on the computeralgebraic system Maple 15.